Polyphasic phenotypic and genetic analysis reveals clonal nature of Xanthomonas axonopodis pv. punicae causing pomegranate bacterial blight. (16th December 2019) - Kumar, A.; Sharma, J.; Munjal, V.; Sakthivel, K.; Thalor, S. K.; Mondal, K. K.; Chinchure, S.; Gharate, R.
Abstract : Yellow‐pigmented bacteria isolated from blight‐affected pomegranate leaves and fruit across seven Indian states in epidemics during the years 2008–2016 were characterized and identified using phenotypic and genotypic tools. All bacterial isolates shared phenotypic traits such as colony morphology, NaCl and pH sensitivity and fuscan production, and caused typical lesions on pomegranate plants upon artificial inoculation. Analysis of 16S ribosomal DNA and 16S–23S rDNA intergenic spacer sequences confirmed their identity as Xanthomonas axonopodis pv. punicae . The new isolates collected after 2000 were compared with an old isolate from the 1950s using polyphasic taxonomic approaches including multilocus sequence analysis (MLSA). Nucleotide polymorphism in 24 isolates for nine genomic loci ( dnaK, fyuA, gyrB (Young), gyrB (Almeida), rpoD, fusA, gapA, gltA and lepA ) showed minor variations in loci fyuA and gyrB. Isolates were grouped into four nearly identical sequence types, ST1, ST2, ST3 and ST4, based on their allelic profiles, ST3 being widespread in Indian states. Molecular phylogenetic analysis of concatenated 5690 bp with other Xanthomonas pathovars revealed its close genetic similarity with the X. citri group . The blight outbreak in diverse geographical locations is attributed to a re‐emerged clonal population of X. axonopodis pv. punicae on a genetically homogenous pomegranate cultivar. The latently infected vegetative planting material of elite pomegranate cultivars contributed to the dissemination of the bacterial inoculum. This study highlights and forewarns of the role played by the clonally propagated elite pomegranate cultivars in disseminating and sustaining clonal populations of this bacterial plant pathogen in many Indian states. Abstract : Genetic and phenotypic analysis reveal clonal nature of Xanthomonas axonopodis pv. punicae in India and key roles played by genetically narrow elite pomegranate cultivars in disseminating blight among the orchards in various states.